The efficacy of acupuncture in relieving postoperative pain in patients with low simple anal fistula: Protocol of a prospective, randomised, controlled trial. - Min Yang; De Zheng; Xingtao Jin; Huili Tang; Weiwei Cao; Qianqian Ye; Yin Qu; Zubing Mei (PLoS ONE)
Background Anal fistula surgery often leads to postoperative pain, which can hinder recovery and negatively impact patients' quality of life. This prospective, randomised, controlled trial (RCT) aims to investigate the efficacy of acupuncture in alleviating postoperative pain and reducing the usage of analgesic medications following anal fistula surgery. Methods This single-centre, patient-blinded, assessor-blinded, placebo-controlled randomised controlled trial (RCT) will be conducted at a tertiary referral hospital. A total of 66 patients with low simple anal fistula will be randomised at a 1:1 ratio to receive either acupuncture or sham acupuncture. The primary outcome is the difference in the numerical rating scale (NRS) pain score before and after acupuncture at 6 hours post surgery. The secondary outcomes include postoperative analgesic usage (Day 0 to Day 7), complications (including infection, urinary retention, and bleeding from Day 0 to Day 7, as well as delayed wound healing and recurrence within 3 months post surgery), sleep quality (PSQI from Day 0 to Day 7), psychological state (SDS and SAS on Day 0, Day 1, and Day 7), and overall recovery quality (QoR-15 on Day 1, Day 3, and Day 7). The statistical analysis of this trial will be conducted using SPSS software, validating the normality of data and the homogeneity of variance, and employing t-tests, Mann-Whitney U tests, chi-square tests, and repeated measures ANOVA to analyze baseline data, primary and secondary outcome indicators. Discussion This study aims to contribute to the expanding evidence base regarding the role of acupuncture in postoperative pain management. Through a comprehensive assessment of pain relief, analgesic usage, and other recovery-related outcomes, our findings will establish a foundation for standardizing acupuncture protocols specifically tailored for anal fistula surgery patients. The strengths of this trial are rooted in its rigorous randomised controlled trial (RCT) design, comprehensive outcome measures, and focused examination of a clinically significant issue. Ultimately, the findings of this trial have the potential to offer valuable insights into the utility of acupuncture as an adjunctive therapy for postoperative pain management among anal fistula patients, thereby informing future clinical practice and research directions. Trial registration This study was registered in the China Clinical Trial Registry on June 1, 2024, with registration number: ChiCTR2400085178.